PENGARUH MODEL SNOWBALL THROWING TERHADAP HASIL BELAJAR PKN DI SEKOLAH DASAR - Apriliani, Tri; Uliyanti, Endang; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the effect of snowball throwing model to student learning outcome in Citizenship Education class V public elementary school 72 Pontianak Barat. The Method used in this research is experiment with forms of experimental design quasi research with the study design nonequivalent control grup. Population in this research is all of fifth grade students public elementary school 72 Pontianak Barat as many as 54 students. The sampling technique in research using probabiliti sampling with a type of random sampling. Data collection technique used is test techniques with multiple choice. Result of the data analyze, obtained an average post-test in experimental class obtained at 78,88 while the control class is 70,06. Result of t test obtained Fcount (9,513)> Ftabel (2,6064), its mean Ha accepted and H0 is rejected, which means the implemantation of inquiry model has influence to student learning outcome in Citizenship Education of class V public elementary school 72 Pontianak Barat.Keywords: The Effect, Snowball Throwing Model, Learning Outcomes, Citizenship Education